Antibacterial activity of phyllospheric bacteria isolated from Rhizophora mucronata against Escherichia coli and Bacillus subtilis - DEBIE RIZQOH; SILVA DWI YOLANDA; ENNY NUGRAHENI; SIPRIYADI SIPRIYADI; MELLYTA ULYANDARI; RIZKY HADI WIBOWO; OKTOVIANI OKTOVIANI; ELLEN MAIDIA DJATMIKO; ANNISA AMELIA PUTRI (Society for Indonesian Biodiversity, 2025)
Abstract. Rizqoh D, Yolanda SD, Nuhraheni E, Sipriyadi, Ulyandari M, Wibowo RH, Oktoviani, Djatmiko EM, Putri AA. 2025. Antibacterial activity of phyllospheric bacteria isolated from Rhizophora mucronata against Escherichia coli and Bacillus subtilis. Biodiversitas 26: 199-210. The treatment of bacterial infection often involves the administration of antibiotics. However, the increasing use of antibiotics has led to bacterial resistance. The black mangrove Rhizophora mucronata is a vital biological resource containing bioactive compounds with potential antibacterial properties. The objective of this study was to investigate the antibacterial potential of phyllospheric bacteria from R. mucronata leaves against Escherichia coli and Bacillus subtilis. The study was carried out using descriptive experimental research. In the initial stage, phylospheric bacteria were isolated from the leaves of R. mucronata using serial dilution method. The results showed that a total of 641 colonies were isolated from R. mucronata. Out of them, 53 dominant phyllospheric bacterial isolates were identified, which exhibit regular round shape with smooth edges colonies, flat elevation, moist texture and produce yellow color pigment. Gram staining revealed 42 Gram-positive and 11 Gram-negative bacterial isolates. The antibacterial activity test showed that 10 isolates had the ability to inhibit the growth of E. coli, 6 isolates inhibited the growth of B. subtilis and 3 isolates inhibited both bactera. Among 19 isolates, three isolates, namely BF1, BF4, and BF17 showed the best antimicrobial activity. The result of phytochemical tests revealed that all the crude extracts contained alkaloid, tannins, and saponins. Gas chromatography-mass spectrometry analysis showed potential metabolites, such as: [3,4-D]pyrimidine-5,7-dione, cyclo (L-Pro-L-Val), maculosin, 2,3,4-Trihydroxybenzaldehyde (TBA), phenethyl alcohol (PEA) tryptophol, benzene ethanol and benzeneacetic acid. The present study concluded that phyllospheric bacteria produce several active compounds that can inhibit bacterial growth.